What kind of public health do we want? - Vilhena, Manuela (2012)
Any modification made by Man has practical consequences in different areas! Interdependence requires promotion of alliances and synergies! In a Global World, we need work together: One World, One Health. Are we training students for the future? What skills do they need? Are we using the best methodologies to promote public health? What more do we need to do? “THE SAPUVETNET III PROJECT Contributing to Millennium Development Goals through the One Health Concept”, EU_ALFA n. DCI-ALA/19.09.01/08/19189/169-157/ ALFA III-75 intends to contribute to the definition of which areas should be teaching in veterinary medicine and what skills students should acquire and contribute in the future to the objectives of the millennium. We want to present you the project and request your contribution to this effort.